2D Inorganic Bimolecular Crystals with Strong In‐Plane Anisotropy for Second‐Order Nonlinear Optics. Issue 32 (26th June 2020) - Feng, Xin; Sun, Zongdong; Pei, Ke; Han, Wei; Wang, Fakun; Luo, Peng; Su, Jianwei; Zuo, Nian; Liu, Guiheng; Li, Huiqiao; Zhai, Tianyou
Abstract: 2D inorganic bimolecular crystals, consisting of two different inorganic molecules, are expected to possess novel physical and chemical properties due to the synergistic effect of the individual components. However, 2D inorganic bimolecular crystals remain unexploited because of the difficulties in preparation arising from non‐typical layered structures and intricate intermolecular interactions. Here, the synthesis of 2D inorganic bimolecular crystal SbI3 ·3S8 nanobelts via a facile vertical microspacing sublimation strategy is reported. The as‐synthesized SbI3 ·3S8 nanobelts exhibit strong in‐plane anisotropy of phonon vibrations and intramolecular vibrations as well as show anisotropic light absorption with a high dichroism ratio of 3.9. Furthermore, it is revealed that the second harmonic generation intensity of SbI3 ·3S8 nanobelts is highly dependent on the excitation wavelength and crystallographic orientation. This work can inspire the growth of more 2D inorganic bimolecular crystals and excite potential applications for bimolecular optoelectronic devices. Abstract : 2D inorganic bimolecular crystals SbI3 ·3S8 nanobelts are successfully prepared by a facile vertical microspacing sublimation strategy. The SbI3 ·3S8 nanobelts show strong in‐plane optical anisotropy with high dichroic ratio up to 3.9 due to the anisotropy of phonon vibrations and intramolecular vibrations. Moreover, the second‐harmonic generation intensity of SbI3 ·3S8 nanobelts exhibits a great dependence on excitation wavelength and crystalline orientation.